A peptoid supramolecular host for benzo[a]pyrene in water. Issue 4 (3rd April 2018) - Fuller, Amelia A.; Tenorio, Kristiana; Huber, Jonathan; Hough, Samuel; Dowell, Kalli M.
Abstract: Studies that identify a new supramolecular host for the highly toxic and prevalent carcinogen benzo[ a ]pyrene (BP) are reported here. By monitoring changes to absorption and fluorescence spectra, the interaction between BP and two peptoids ( N -substituted glycine oligomers) of different length and self-association propensities were compared. Peptoid length and solvent choice influence spectral features. Observed trends support that peptoid self-association in aqueous solution generates a hydrophobic core to which BP can associate. Abstract :